2017
DOI: 10.1016/j.biopsycho.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support predicts lower cardiovascular reactivity to stress in older adults

Abstract: The benefits of perceived social support for physical and psychological health are well-established. However, little research has explored associations between perceived social support and cardiovascular reactivity in older adults. This exploratory study recruited a sample of older adults (M=69years, SD=5.62) and examined quality and quantity of perceived social support as predictors of cardiovascular reactivity to laboratory-based stress (N=39 participants) and ambulatory cardiovascular activity in everyday l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 31 publications
0
17
2
1
Order By: Relevance
“…Previous studies have suggested that perceived self‐efficacy was in relation to the reduction in stress and the impact on mental health (Burger & Samuel, 2017; Schonfeld et al, 2017). In addition, perceived social support, that is the emotional experience of the individual feeling supported, respected and understood, is regarded as one of the important mediating factors that determine the relationship between psychological stress and health (Howard et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that perceived self‐efficacy was in relation to the reduction in stress and the impact on mental health (Burger & Samuel, 2017; Schonfeld et al, 2017). In addition, perceived social support, that is the emotional experience of the individual feeling supported, respected and understood, is regarded as one of the important mediating factors that determine the relationship between psychological stress and health (Howard et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the mothers, we found greater acculturation and resilience factors (e.g., higher subjective social status, higher social support), associated with lower cardiometabolic risk, but little evidence that stress associated with either BMI or BP. A substantial literature supports associations between social support and BP and BMI; e.g., social support has been associated with lower BP reactivity to laboratory stress in older adults ( 70 ) and was protective against intergenerational transmission of obesity in a study of Finns in mid-adulthood ( 71 ). Findings with acculturation are more mixed.…”
Section: Discussionmentioning
confidence: 99%
“…Su influencia en esta área se caracteriza por intervenir en la disminución del estrés, modulando la presión sanguínea, generando efectos sobre el sistema inmunológico y endocrino de las personas, y promoviendo conductas saludables como evitar consumir alcohol, drogas ilícitas, hacer dieta y realizar ejercicio, entre otros (Pacheco, Suárez, & Angelucci, 1998). Algunos estudios refieren el efecto directo que tiene el apoyo social percibido sobre la salud física y psicológica (Howard, Creaven, Hughes, O'leary, & James, 2017;Jung et al, 2016;Novoa, & Barra, 2015), otros destacan el efecto moderador que tiene sobre el estrés (González, & Estévez, 2017), y algunos autores manifiestan su relación indirecta sobre la salud, a través de otras variables como la resiliencia (Leiva, Pineda, & Encina, 2013) y la autoeficacia (Miao, Feng, Wu, Zhang, Ge, & Pan, 2015).…”
Section: Introductionunclassified